Optimization of measurement points choice in preparation of green areas acoustic map = Optymalizacja wyboru punktów pomiarowych w opracowaniu map akustycznych terenów zielonych - Sztubecka, Małgorzata; Bujarkiewicz, Adam; Sztubecki, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to analyze the selection of measuring points of sustainable sound level in the spa park. A set of points should allow to make on their basis an acoustic climate map for the park at certain times of day by usage available tools. Practical part contains a comparative analysis of developed noise maps, taking into account different variants of the distribution and number of measuring points on the selected area of the park.
Keywords: maps; acoustic maps; noise; green areas; mapa; mapa akustyczna; hałas; tereny zielone